9x-3=6x-48

Simple and best practice solution for 9x-3=6x-48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-3=6x-48 equation:



9x-3=6x-48
We move all terms to the left:
9x-3-(6x-48)=0
We get rid of parentheses
9x-6x+48-3=0
We add all the numbers together, and all the variables
3x+45=0
We move all terms containing x to the left, all other terms to the right
3x=-45
x=-45/3
x=-15

See similar equations:

| 5(x+2)=3x-(6-x) | | (-3)-x=12 | | 4x-4=3x-3.5x | | F=9c÷5+32 | | x/2=12.8 | | X-1/3=3x/5 | | 24=x-16 | | 5/6-8/15=x | | 1.77x=29 | | n^2+40n+60=0 | | 16x=x+16 | | (1.07)*x+0.2*(1.07)x=41 | | 2.4+x=19.3 | | X(5-2x)+15=0 | | 8x-3=2x+0 | | 1×(3x-10)=3x-10 | | 3(2x-1)=2x+35 | | x+0.07x+0.07(x+0.07x)=21 | | 75+2a=40+2,1a | | 75+2a=40+2,1 | | x/3+4=-3x+2 | | x+0.07x+0.15(x+0.07x)=25 | | 3t^2-6t-10=10 | | ((x-100)/x)*100=150 | | 1/7x+2=1 | | x+0.07x+0.15(x+0.07*x)=25 | | ½x+4=20 | | (2x-5)/7=(3x-6)/4 | | x=1.5x+100 | | -0.5x+9.5=0x+5 | | x+0.07+0.15(x+0.07)=25 | | 21-6×=9(3-x) |

Equations solver categories